2022
DOI: 10.31234/osf.io/kymqn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How and When Managers Reward Employees’ Voice: The Role of Proactivity Attributions

Abstract: Recent voice research has noted that providing adequate job rewards for speaking up can sustainably motivate voice from employees. We examine why managers who seek out voice at work might not always properly reward the behavior. Drawing on theories of dispositional attribution, we propose that, in general, managers tend to reward voice because it signals to them that employees possess a valued underlying trait: proactivity, which is characterized by change-orientation and foresight. However, we argue that when… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…First, previous research has shown that leadership has an encouraging role in employee voices (Howard & Holmes, 2020;Park et al, 2022), but our research advances existing employee voice types by showing different leadership styles. Supported Hypothesis 1 states that leadership style plays a more critical role in determining the employee's voice on the job.…”
Section: Contributionsmentioning
confidence: 71%
See 4 more Smart Citations
“…First, previous research has shown that leadership has an encouraging role in employee voices (Howard & Holmes, 2020;Park et al, 2022), but our research advances existing employee voice types by showing different leadership styles. Supported Hypothesis 1 states that leadership style plays a more critical role in determining the employee's voice on the job.…”
Section: Contributionsmentioning
confidence: 71%
“…When leaders remove barriers to hierarchical communication (Lapointe and Vandenberghe, 2018), they create an organizational climate of trust and psychological safety where employees feel safe not only to share advice with colleagues, but more importantly to ask work-related questions (Weiss et al, 2018). Leader personality traits may have indirect effects, positive or negative, on members' voice and work engagement with workplace status (Carnevale et al, 2022;Park et al, 2022;Wang et al, 2022). Research has found that leaders' threats to judge employees' voices can lead to lower performance appraisals of employees (Weiss & Morrison, 2019;Xu et al, 2019), so employees may change their voiceover styles in line with their supervisors' perceptions of workplace behavior (Ng et al, 2022; Park et al, 2022.…”
Section: Leadership Stylesmentioning
confidence: 99%
See 3 more Smart Citations